Formulasi Dan Evaluasi Sediaan Hand Body Lotion Ekstrak Biji Bunga Matahari (Helianthus annus L.) - I.A.K. Pramushinta; P.T. Hardani (FMIPA : Universitas PGRI Adi Buana, 2021)
Sunflower (Helianthus annus L.) is a plant that has many benefits. The oil in sunflower seeds contains unsaturated fatty acids in the form of oleic and linoleate morethan soybean, peanut, corn and palm oil. Sunflower seed oil is also reported to be used as a base for hand body lotions. This study aims to make a Hand Body Lotion formulation from sunflower seed extract and then evaluated. The evaluations carried out were pH, homogeneity, color and odor. The results of pH evaluation showed that there was a change in the pH of each formula which was still in the pH range of the topical preparations 4.5-8 according SNI. While the best homogeneity test results in formula II when compared to formulas I and III are due to clumping in formulas I and III. The test results on the smell and color of the Hand Body Lotion did not change with the opinions of 35 respondents. Keywords:Hand Body Lotion, Sunflower Seed Extract, Semisol